Formulation and solution of distribution system voltage and VAR control with distributed generation as a mixed integer non-linear programming problem - Paaso, Esa A.; Liao, Yuan; Cramer, Aaron M. (Electric power systems research, 2014)
•A new voltage and VAR control method is developed.•Distributed generation is utilized for optimizing voltage and VAR control.•Mixed integer non-linear programming is used to model the problem. Coordinated voltage and VAR control (VVC) can provide major economic benefits for distribution utilities. Incorporating distributed generations (DG) for VVC can improve the efficiency and reliability of distribution systems. This paper presents an approach to formulate and solve distribution system VVC with DG units as a mixed integer non-linear programming (MINLP) problem. The method can be utilized to create an effective control scheme for both the traditional VVC devices and DG units. The MINLP formulation is based on three-phase power flow formulation, and is solved with an open-source BONMIN optimization solver with outer approximation (OA) algorithm. BONMIN is interfaced with Matlab via a third-party optimization toolbox. The proposed approach is applied to several distribution feeder models with promising results.